Kemampuan Dasar Smash dalam Permainan Bola Voli Menggunakan Metode Permainan pada Siswa Ekstrakurikuler SMA N 1 Kedung Waringin - Fajri, Muflikhul (Lentera: Jurnal Ilmiah Kependidikan, 2017)
This study aims to determine the effect of the Smash basic ability in Volleyball Game using Games Method in Extracurricular Students of SMAN 1 Kedung Waringin. Based on the research results and the results of statistical calculations to the hypothesis testing, it is obtained that initial results obtained Smash Ability Test score number is 2999, the average score is 99.97, standard deviation is 12.93 and varian standard is 167.27 while the final test score number is 3709, the average score is 123.63, a standard deviation is 15.02 and variant standar is 225.55, and to increase the number of earned value is 710, average score is 23.67 standard deviation is 27.95 and variants is 5.29. Smash basic ability in Volleyball Game using Game Method in Extracurricular Students of SMAN 1 Kedung Waringin increases after being treated Using Games Method. This is evidenced by the test results showing the significance of the results, that is t cal (24.40) > t table (1.70).